Studying the Physical and Chemical Properties of Polymethyl Methacrylate / Hydroxyapatite Composite for Bone Tissue Engineering - Madlol, Reman F.; Abed, Iman J.; Thahab, Sabah M. (Journal of Engineering and Sustainable Development, 2025)
The influence of particle aggregation in polymer composite materials is generally affected by polymer-based properties. This study synthesizes polymethyl methacrylate polymers in three concentrations to evaluate their rheological properties at 25 °C. The viscosity and pH of Polymethyl methacrylate PMMA pure and composite polymer solutions are tested. In pure PAMM/acetone, pH increased from 5.3 to 5.4 and then decreased to 4.8 as PMMA increased. PMMA viscosity rises from 17.5 to 32.2 cp, and thermal conductivity falls from 0.301 to 0.205 W/m.K. Hydroxyapatite nano and micro particles with weight ratios of 0.125, 0.25, and 0.5 wt.% are added to PMMA polymer for experiments. Increased micro hydroxyapatite in PMMA raises acidity-base values from 6.91 to 7.15. The acidity drops from 7.12 to 7.00 with nano-hydroxyapatite. The viscosity of the PMMA/HAP composite increases from 17.3 to 18.1 cp for micro-particle size and from 18.1 to 19.1 cp for nanoparticle size as HAP weight ratios increase. With increased micro and nano HAP particle size in polymer composites, thermal conductivity increases from 0.155 to 0.225 W/m · K and from 0.163 to 0.183 W/m·K.